P0802RELATIONSHIP BETWEEN RENAL INSUFFICIENCY AND AIRFLOW LIMITATION AND THEIR IMPACT ON MORTALITY IN A COMMUNITY-BASED POPULATION: THE YAMAGATA (TAKAHATA) STUDY. (6th June 2020) - Miyata, Masahiro; Tanaka, Tomomi; Suzuki, Natsuko; Kudo, Kosuke; Ichikawa, Kazunobu; Inoue, Sumito; Watanabe, Masafumi; Kayama, Takamasa; Konta, Tsuneo
Abstract: Background and Aims: Chronic kidney disease and chronic obstructive pulmonary disease (COPD) are known risk factors for mortality. In this study, we investigated the association between renal deficiency and airflow limitation that characterizes COPD, and its effect on 10-year mortality in a community-based population. Method: The study subjects were 1, 233 health check-up participants (mean age 64 years; 46.7% men). We defined renal insufficiency as GFR <60 mL/min/1.73m 2 estimated using serum creatinine (Cr) or cystatin C (CysC), and airflow limitation (AFL) as forced expiratory volume in 1 second to forced vital capacity ratio <70% on spirometry. Results: The prevalence of Cr-based and CysC-based renal insufficiency, and AFL in total subjects was 6.6%, 14.8%, and 11.2%, respectively. Compared with subjects without AFL, those with AFL showed a significantly higher prevalence of CysC-based renal insufficiency (24.6% vs. 13.5%, P <0.01), but not of Cr-based renal insufficiency (8.0% vs. 6.4%, P =0.77). The prevalence of CysC-based renal insufficiency was increased, along with the progression of AFL severity (P for trend <0.01). During the follow-up period, there were 154 (12.5%) deaths. Cox proportional hazard analysis adjusted for confounders showed that the hazard ratio (95% confidence interval) for all-cause mortality was 1.76 (1.12-2.71) in subjects with CysC-based renal insufficiency alone, 1.13 (0.62-1.94) in those with AFL alone, and 2.30 (1.20-4.18) in those with both CysC-based renal insufficiency and AFL, with subjects without both CysC-based renal insufficiency and AFL as the reference. In contrast, the adjusted hazard ratios for all-cause mortality did not reach statistical significance in subjects with both Cr-based renal insufficiency and AFL, with subjects without both Cr-based renal insufficiency and AFL as the reference. Conclusion: This study showed that CysC-based renal insufficiency and AFL are strongly associated and that their overlap is a significant risk for mortality in community-based populations.